METHODS OF STUDYING THE CONCEPT «CHILD» - Khujamberdiyeva Gavhar Ilhom kizi (Innovate Conferences, 2025)
This article is devoted to the linguocultural analysis of the concept “child.” The research highlights the importance of studying this concept from the perspectives of linguistics, cultural studies, and psycholinguistics. The paper employs key methodological approaches including semantic analysis, discursive approaches, psycholinguistic experiments, and contextual analysis.
Keywords: child concept, linguoculturology, semantic analysis, discursive approach, psycholinguistic experiment, phraseological analysis, cultural studies, lexical expression, contextual analysis, linguistics.